Influence of edible flower inclusion on the nutritional and flavor changes of fermented pear wine - Yang, Mingjing; Wang, Jintao; Li, Li; Xiong, Qirui; Li, Xiaofei; Zhou, Xuhong (Frontiers in Nutrition, 2025)
Compound-fermented wines integrate the aromas, flavor compounds, and nutritional components from several raw materials, enriching the flavor and texture of the final product. This study aimed to explore the influence of edible flowers on the quality of pear wine by evaluating the total phenol and flavonoid contents, antioxidant capacities, and tyrosinase inhibition abilities during the mixed fermentation of pears (P) with Rosa rugosa (PR), Dendrobium candidum (PD), Chrysanthemum morifolium (PC), Lonicera japonica (PL), and Osmanthus fragrans Lour (PO), using standard methods The findings revealed that total phenol and flavonoid contents, antioxidant capacities, and tyrosinase inhibition abilities significantly increased in compound pear-flower wine. Specifically, total polyphenol content (TPC), total flavonoid content (TFC), the DPPH(1,1-diphenyl-2-picryl-hydrazyl radical) radical scavenging activity (DRSA), Trolox equivalent antioxidant capacity (TEAC), and ferric reducing antioxidant power (FRAP) for PR were 580.69 ± 9.51 mg of gallic acid equivalents (GAE) per liter of the sample (mg GAE/L), 600.05 ± 36.6 mg of rutin per liter of the sample (mg RE/L), 0.51 ± 0.00 μmol of Trolox equivalents (TE) per milliliter (μmol TE/mL), 10.11 ± 0.06 μmol TE/mL and 6.35 ± 0.35 μmol of Fe2+ equivalents (FE) per milliliter (μmol FE/mL), respectively. Additionally, we further analyzed the volatile and non-volatile components of P and PR at different fermentation stages. A significant difference was observed between the non-volatile and volatile metabolites, with pear rose wine (PRW) demonstrating superior characteristics compared with pear wine (PW). Phenolic acids and flavonoids were closely associated with the formation of non-volatile metabolites, while esters, hydrocarbons, alcohols, and ketones were significantly linked to volatile formation. Notably, 2(5H)-furanone, 5-ethyl-3-hydroxy-4-methyl-, emerged as a significant aroma contributor with a relative odor activity value (ROAV) of 236,348.11, giving a sweet, fruity, nutty taste. Compared with PR, decanoic acid ethyl ester increased 634.67-fold in PRW. These findings provide a foundation for further exploration into optimized fermentation protocols, mechanistic studies on flavor and bioactive compound formation, and potential commercial applications in the functional beverage industry.